Association between psychiatric disorders and the risk of stroke: a meta-analysis of cohort studies - Hu, Zhonghou; Sun, Weishan; Cui, Enxiu; Chen, Bo; Zhang, Mi (Frontiers in Neurology, 2024)
BackgroundPsychiatric disorders may be associated with an elevated risk of stroke; however, the existence of variations in this association between different populations remains controversial. Consequently, we conducted a comprehensive systematic review and meta-analysis to examine the magnitude of the relationship between psychiatric disorders and the risk of stroke.MethodsThe PubMed, Embase, and Cochrane Library databases were systematically searched to identify eligible studies from inception to April 2024. The aggregated findings were expressed as relative risks (RRs) with 95% confidence intervals (CIs), and the combined analysis was performed using a random-effects modeling approach. Further exploratory analyses were also performed using sensitivity and subgroup analyses.ResultsA total of 36 cohort studies, involving 25,519,635 individuals, were selected for analysis. We noted that depression (RR: 1.50; 95% CI: 1.34–1.68; p < 0.001), schizophrenia (RR: 1.74; 95% CI: 1.36–2.24; p < 0.001), and bipolar disorder (RR: 1.65; 95% CI: 1.27–2.14; p < 0.001) were associated with an elevated risk of stroke. Further exploratory analyses found that the association between depression and the risk of stroke differed according to the adjusted level (RR ratio: 0.77; 95% CI: 0.61–0.98; p = 0.034), and the association between schizophrenia and the risk of stroke differed according to the outcome definition (RR ratio: 0.68; 95% CI: 0.52–0.90; p = 0.006). Moreover, the association between bipolar disorder and the risk of stroke differed according to the study design (RR ratio: 0.68; 95% CI: 0.55–0.84; p < 0.001).ConclusionThe significant association between psychiatric disorders and an elevated risk of stroke highlights the importance of enhanced monitoring and stroke prevention in patients with psychiatric disorders.Systematic review registrationOur study was registered on the INPLASY platform (number: INPLASY202450049).